Prevalence of crashes and associated factors among commercial motorcycle riders in Bamenda, Cameroon. (March 2021) - Wankie, Che; Al-Delaimy, Wael; Stockman, Jamila; Alcaraz, John; Shaffer, Richard; Hill, Linda
Abstract: Introduction: Crash-related injury and fatality tends to be disproportionately higher among motorcycle riders compared to other types of motor vehicle users due to the absence of passive safety vehicle components of other vehicles. Methods: A population-based cross-sectional study among consenting commercial motorcycle riders conducted in Bamenda, Cameroon estimated the prevalence (commercial motorcycling lifetime and past 12-months) of self-reported crashes and examined contributing factors associated with crashes. Results: Among 552 participants, 77.4% self-reported a crash over lifetime as a commercial motorcycle rider. The prevalence of self-reported crash within the past 12 months was 21.5%. The odds of lifetime crash involvement were higher among riders with 3-4 years (Adjusted Odds Ratio [AOR] = 2.14; 95% CI = 1.14–4.01) or five years (AOR = 3.15; 95% CI = 1.73–5.73) of riding experience who typically carried more than two passengers (AOR = 3.57; 95% CI = 1.18–10.84). After adjusting for age, education level, marital status, and smoking status, riders were at increased odds of a self-reported severe crash of single-vehicle collision type if they typically used alcohol (AOR = 2.14, 95% CI = 1.22–3.76), rode on roads that were unpaved (AOR = 4.33, 95% CI = 2.50–7.52), muddy (AOR = 5.90, 95% CI = 1.60–21.73) or pothole-ridden (AOR = 2.41, 95% CI = 1.18–4.95), and at estimated speeds of 45 km/h or more (AOR = 2.55, 95%CI = 1.28–5.09). Conclusion: Occurrences of road traffic crashes are frequent among commercial motorcycle riders who use alcohol, typically carry multiple passengers, speed, and ride on poor road conditions. Intervention efforts should focus on strategies to minimize crash-related injuries and fatalities by improving rider safety, infrastructure, and implementing effective road traffic policies. Highlights: This primary study estimated crash prevalence of commercial motorcycle riders in Bamenda, Cameroon. Determinants associated with motorcyclists' behavior and poor road conditions were identified. Rider training courses, education, and traffic policies are necessary countermeasures.